ANTESEDEN DAN KONSEKUENSI NIAT MEMBAYAR ZAKAT PENGHASILAN - Willy Nurhayadi; Agus Ismaya Hasanudin; Tenny Badina (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2017)
The purpose of this study was to analyze the influence of Attitude, Subjective Norms, Level Worship, Zakat Knowledge, Confidence Level, The Perceived Behavioral Control on Behavioral Intention and also Its Perceived Behavioral Control and Intention to Conduct Compliance Income Zakat. The data used in this study was obtained from the university in the city of Serang, Banten. The data were processed using the software program Statistical Product and Service Solutions (SPSS). This study used a purposive sampling method to sample accounting lecturer. Source of data obtained from the field research, in particular by distributing questionnaires to obtain primary data. The results showed (1) attitude affect the Intention Behavior, (2) Subjective Norm has no effect on Behavioral Intention, (3) Levels of Worship has no effect on Behavioral Intention, (4) Knowledge of Zakat no effect on Behavioral Intention, (5) Level of Confidence no effect on Behavioral intention, (6) The perceived Behavioral Control effect on Behavioral intention, (7) The perceived Behavioral Control has no effect on Zakat Income Compliance, and (8)Behavioral intention affect the Zakat Income Compliance.